Novel weight loss diet attenuates dietary-induced obesity in mice and might correlate with altered gut microbiota and metabolite profiles - Yang, Xinli; Bao, Li; Zhang, Ying; Long, Jianglan; Li, Yan; Wang, Huijun; Cui, Yan; Yan, Dan (Frontiers in Nutrition, 2022)
Although many dietary patterns have been studied for weight loss, various limitations still exist. Therefore, we designed a novel weight loss diet (NWLD) with carbohydrate, protein, and fat (energy) contents of 45, 20, and 35%, respectively. The saturated fatty acids: monounsaturated fatty acids:polyunsaturated fatty acids ratio was 1:2:1, and the insoluble: soluble dietary fiber ratio was 2:1. We aimed to observe the effect of NWLD on weight loss and understand the underlying metabolic mechanisms. Twenty-nine male C57BL/6J mice were selected. Nine mice were fed ordinary feed in a blank control group, and the rest were fed a high-fat diet (HFD) to establish obese mouse models. Twelve weeks later, obesity models were established, and ten obese mice were switched to NWLD feeding. Six weeks after switching the diet, the serum and intestinal feces of mice were collected, obesity-related indicators, gut microbial composition, and fecal metabolite profiles of all the mice were determined, and the correlations among these indicators were analyzed. The results showed that the NWLD attenuated HFD-induced weight gain, serum triglycerides, and inflammatory factors, optimized the body composition, and corrected the altered gut microbiota composition. Amino acid metabolism pathways and metabolites might play key roles in this process. The findings of this research imply that NWLD could be an effective nutritional remedy for managing dietary-induced obesity.